Analysis of sugar-binding sites in mammalian cell nuclei by quantitative flow microfluorometry. - Sève, A P (1986)
Quantitative flow microfluorometry of neoglycoprotein (bovine serum albumin coupled to sugar and to fluorescein) binding demonstrated the existence of sugar-binding sites (i.e., lectin-like molecules) in isolated BHK cell nuclei. The very similar labeling intensities obtained with nuclei isolated by cell lysis and with permeabilized karyoplasts obtained by enucleation strengthened the idea that the binding sites are borne by actual nuclear structures and not by cytoplasmic or membrane-derived contaminants. With both nuclei-isolation procedures, neoglycoproteins (containing similar numbers of sugar residues) used as markers can be similarly classified. Fluorescence microscopy further indicated that in both nuclear preparations, the neoglycoprotein binding sites were associated with the nucleoli as well as with nucleoplasmic ribonucleoprotein elements. Nuclei from exponentially growing cells bound much greater amounts of neoglycoprotein than did nuclei from contact-inhibited cells.